The Physicochemical and Sensory Properties of Gluten-Free Brownies Produced using Purple Yam Paste (Dioscorea alata) and Mocaf - Ramadani, Suci Putri; Rahmawati, Medina Alia; Pratami, Tesy; Sulistiana, Ika Putri; Yusfi, Liza Aulia; Pamungkas, Putra; Nazarudin, Nazarudin; Ulyarti, Ulyarti (Jurnal Bio-Geo Material Dan Energi, 2025)
The development of gluten-free brownies with purple yam paste and mocaf is an alternative for individuals who avoid consuming gluten. This study aims to determine the effect of the ratio of purple yam paste and mocaf on the characteristics of brownies. A Randomized Block Design was used with six treatment levels of purple yam paste to mocaf ratios: 0:100, 15:85, 30:70, 45:55, 60:40, and 75:25. Each treatment was replicated three times. The data obtained were analyzed using Analysis of Variance. If a significant effect was found, the analysis was continued using Duncan new Multiple Range Test (DnMRT) at the 5% level. The results showed that the ratio of purple yam paste to mocaf significantly affected the texture, color, and the hedonic organoleptic qualities of texture and color. The best treatment was the 75:25 ratio which resulted in a texture force of 105.5 N, water content of 20.16%, and color values of L* 37.1 a* 7.8 b* -2.9. Organoleptic scores for this treatment were: texture 3.48 (rather soft), color 4.40 (purple), taste 4.00 (like), overall acceptance 4.04 (like). However, texture and overall acceptance were lower than commercial brownies. The nutritional composition of this treatment included an ash content of 1.42%, protein content of 4.82%, fat content of 29.12%, and carbohydrate of 44.49%.